MODEL PEMBELAJARAN LEARNING CYCLE 5E SEBAGAI PENDEKATAN UNTUK MENINGKATKAN MOTIVASI BELAJAR: SEBUAH PENELITIAN EKSPERIMEN - Nurilmi; Siti Zulaikhah; Uswatun Hasanah (Jurnal Bilqolam Pendidikan Islam, 2026)
This research investigates the effectiveness of the Learning Cycle 5E instructional model in improving students’ learning motivation in the Akidah Akhlak subject at MAN 2 Bandar Lampung. The study was conducted in response to students’ low motivation, which is attributed to the predominance of conventional teaching practices, insufficient instructional media, and limited interaction between teachers and learners. A quasi-experimental approach employing a posttest-only control group design was applied. Participants were chosen through simple random sampling, assigning Class X B as the control group and Class X C as the experimental group. Data were obtained using a 15-item non-test questionnaire that had been validated and demonstrated high reliability, with a coefficient of 0.82. Statistical analysis was performed using a t-test. The findings reveal that the implementation of the Learning Cycle 5E model significantly enhances students’ learning motivation, as evidenced by increased engagement, strong curiosity, and responsible learning behavior. These results underscore the necessity of innovative pedagogical strategies in Islamic education.